Financial Management Accountability In Allocation Of Village Funds (Case Study In Village X) - Sari Mustika Widyastuti; Syahri Syahri (UNIVERSITAS PGRI YOGYAKARTA, 2025)
AbstractThe economic development program in Indonesia can be realized by starting from the smallest part. This can be done by adequately implementing accountability for managing village funds from small villages. This study then aims to see how the implementation of village fund management accountability in village X follows regulations from PERMENDAGRI Number 20 of 2018. This research will be conducted with a qualitative methodology and data obtained from numerous research results and prior studies that are still pertinent to this research. The results of this study found that the implementation of village programs and financial management in village X already had a transparent and accountable nature. However, there are still some obstacles to implementation, such as delays in disbursing funds from local governments. Although it has several shortcomings, the village fund allocation management process has been running following PERMENDAGRI Number 20 of 2018.Keywords: Village Fund Allocation, Accountability, Village Financial Management.